Flotation of Carbonaceous Matter from a Double Refractory Gold Ore: The Effect of MIBC on Flotation Performance and Kinetics - Sugyeong Lee (Minerals, 2021)
The use of alkaline pressure oxidation to pretreat refractory gold ore often results in insufficient gold recovery (<60%) in downstream thiosulfate leaching. To improve gold recovery, flotation was considered for the separation of carbonaceous matter (C-matter). In this study, the effect of MIBC on C-matter flotation was investigated to understand the role of the frother in bubble and froth formation and on flotation kinetics. MIBC dosages between 30 and 150 g/t were used in combination with 500 g/t of kerosene as a collector. The results showed that the recovery and selectivity of C-matter were improved with increasing MIBC dosages. Improved selectivity at higher MIBC dosages was attributed to faster C-matter recovery as bubble size decreased to the critical coalescence concentration (CCC) and to changes to the foam structure. Analysis of flotation kinetics showed that the flotation rate increased as the MIBC dosage increased due to the decreasing bubble size and the reduced induction time caused by the interaction between the collector and the frother. The results of this study explain the role of MIBC in C-matter flotation and can be used as a design basis for scavenger-cleaner flotation testing. Overall, the results show the potential for flotation as a means to improve gold recovery in thiosulfate leaching through the removal of C-matter.